Immersed photovoltaic panels experiment for offshore maritime application - Ivan, Tudorel; Cristea, Ovidiu; Popescu, Mihai-Octavian (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Due to the accelerated growth of worldwide interest in renewable energies, there is currently an impressive documentary base in this field, accumulated as a result of prolific research activity by engineering teams from countries around the world. However, the naval field has been very little touched by these researches and implicitly the recorded results are rare, which justifies us to say that the application of renewable energies in this field is at its early stage and requires more attention from researchers.